An Epidermoid cyst of the upper lip in a completely edentulous geriatric female: A rare case with clinicoradiological report (Indian Journal of Case Reports, 2020)
Epidermal cysts are intradermal or subcutaneous (non-odontogenic), developmental pathologies occurring in the head and neck region with an incidence ranging from 1.6% to 6.9%. They represent <0.01% of all oral cavity cysts. An epidermoid cyst presents as a slow-growing, asymptomatic mass, usually diagnosed only after they have reached a considerable size. Here, we present a rare case of a giant palpable mass in the upper lip in a completely edentulous geriatric female. This report highlights the clinical presentation, imaging findings, and differential diagnosis.